War with Outsiders Makes Peace Inside - Johannes Münster; Klaas Staal (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
In many situations there is a potential for conflict both within and between groups. Examples include wars and civil wars and distributional conflict in multitiered organizations like federal states or big companies. This paper models such situations with a logistic technology of conflict. If individuals decide simultaneously and independently about the amount of internal conflict, external conflict and production, there is typically either only internal conflict, or only external conflict - but not both. If each group decides collectively how much each member has to put into the external conflict before the members individually decide on the amounts put into the internal conflict and production, groups choose sufficiently high external conflict in order to avoid internal conflict. This is a model of the diversionary use of force. We also study the optimal number of groups.
urn:nbn:de:bvb:19-epub-13476-3
Keywords: D72; D74; H11; H74; 330; conflict; war; rent-seeking; hierarchy; federalism; diversion